Bilateral acute retinal necrosis during treatment with alemtuzumab for multiple sclerosis. Issue 4 (July 2022) - Menean, Matteo; Marchese, Alessandro; Bordato, Alessandro; Battista, Marco; Bandello, Francesco; Modorati, Giulio; Miserocchi, Elisabetta
Introduction: Alemtuzumab is a humanized monoclonal antibody used as a treatment of multiple sclerosis (MS) and chronic lymphocytic leukemia. It decreases T cell count leading to significant immunosuppression, with increased risk of systemic and ocular infections. Herein, we report a unique case of bilateral acute retinal necrosis (ARN) caused by varicella-zoster virus (VZV) in a patient affected by MS under treatment with alemtuzumab. Case description: A 36-year-old man with a relapsing-remitting MS under treatment with alemtuzumab developed bilateral visual loss. Anterior segment examination displayed granulomatous keratic precipitates and 3+ cells in the anterior chamber, while fundoscopy showed bilateral 1+ vitritis and peripheral retinal necrosis, complicated by retinal detachment in the left eye. The high viral load for VZV in aqueous humor samples had a univocal interpretation for viral reactivation. In addition to systemic therapy with acyclovir, the patient was treated with bilateral intravitreal injections of foscarnet and underwent pars-plana vitrectomy and silicone oil tamponade for retinal detachment in the left eye. Conclusion: This report shows a unique case of bilateral ARN caused by VZV associated with alemtuzumab. Any visual loss in MS patients under biologic therapy should not be underestimated, performing an accurate differential diagnosis with optic neuritis.